Cutaneous squamous cell carcinoma: an epidemiological review. (16th February 2017) - Green, A.C.; Olsen, C.M.
Abstract : What's already known about this topic? Cutaneous squamous cell carcinoma (SCC) is a common cancer mostly caused by excessive exposure to solar ultraviolet radiation and immunosuppression. What does this study add? The epidemiology of cutaneous SCC is reviewed in detail, integrating available evidence regarding the natural history, population‐based incidence rates, causes and prevention. These skin cancers impose a largely unrecognized burden in white populations but are preventable by sun protection measures, restriction of indoor tanning and possibly by several chemopreventive agents. Respond to this article Summary: Cutaneous squamous cell carcinoma (SCC) is a common cancer in white populations and its disease burden is often substantially underestimated. SCC occurs more often in men than women and increases dramatically with age; those affected often develop multiple primaries over time, which increases the burden. The main external cause is solar ultraviolet radiation (UVR), with immunosuppression being the other established risk factor, shown by the high SCC rates in organ transplant recipients. Sunbed use and certain genetic disorders and medical conditions are also associated with SCC, while associations with human papillomavirus infection and high bodyweight are not established. The presence of actinic keratoses (AKs) on sun‐damaged skin is one of the strongest predictors of SCC in unaffected people and a very small proportion of AKs are SCC precursors, although the true rate of malignant transformation of AKs is unknown. The mainstay of SCC prevention is protection of the skin from undue sun exposure by use of clothing cover and sunscreen during summer or in sunny places. Educational, behavioural and multicomponent interventions directed at individuals ranging from parents of newborns, to school children and adolescents, to outdoor workers, have repeatedly been shown to be effective in improving sun‐protective behaviours. Health policies can facilitate SCC prevention by setting standards for relevant behaviours to reduce UVR exposure, for example, by legislated restriction of the tanning industry. Skin cancer prevention initiatives are generally highly cost‐effective and public investment should be encouraged to control the growing public health problems caused by SCC.